2010
DOI: 10.2340/00015555-0919
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Risk Among Solid Organ Recipients: A Nationwide Cohort Study in Denmark

Abstract: This study assessed the risk of skin cancer following transplantation of 4 types of solid organs, and the risk of skin cancer in patients with chronic diseases that lead to organ transplantations. A population-based cohort of 5279 Danish patients who underwent heart, lung, renal and liver transplantation, and 77,782 patients with chronic heart, lung, renal and liver diseases during 1977-2006 were included in the study. Linkage to the Danish Cancer Registry allowed complete follow-up for basal cell carcinoma, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
4
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 24 publications
5
86
4
2
Order By: Relevance
“…There is, however, no conclusive evidence regarding the causal role of HPV in actinic keratosis at this time. Additional evidence for the role of HPV comes from a study on post-transplant SCC that occurred in a cohort of 500 recipients of allografts; HPV DNA could be detected in nearly 50% of all SCCs (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, no conclusive evidence regarding the causal role of HPV in actinic keratosis at this time. Additional evidence for the role of HPV comes from a study on post-transplant SCC that occurred in a cohort of 500 recipients of allografts; HPV DNA could be detected in nearly 50% of all SCCs (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al reported an SIR of 5.6 for BCC and 113 for SCC (ref. 7 ). In our study it was not possible to calculate adjusted risk for different types of NMSC, as data in the external group do not specify the exact type of NMSC.The relatively low incidence of skin cancer in a cohort of HTRs was recorded by Rinaldiet al or Park et al in a single centre in Korea 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32] Immunosuppressive drugs were a specific exclusion from this study because the increased risks of skin cancer for patients on long-term immunosuppression are profound. 33,34 To reveal a potential role of dietary furanocoumarins and antioxidants, we included a short dietary section in the questionnaire asking participants to report if they regularly (three or more times per week) took any of the following foods known to contain furanocoumarins: celery, celeriac, parsnips, lemons ⁄limes and carrots. 35 Likewise, consumption of antioxidant-rich food items like figs, tomatoes, red grapes ⁄red wine, blackcurrants or other red berries, pomegranate, green tea, soyabeans or antioxidant supplements was assessed.…”
Section: Questionnairementioning
confidence: 99%